6x+5=0.5(13x-3)

Simple and best practice solution for 6x+5=0.5(13x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+5=0.5(13x-3) equation:



6x+5=0.5(13x-3)
We move all terms to the left:
6x+5-(0.5(13x-3))=0
We calculate terms in parentheses: -(0.5(13x-3)), so:
0.5(13x-3)
We multiply parentheses
6.5x-1.5
Back to the equation:
-(6.5x-1.5)
We get rid of parentheses
6x-6.5x+1.5+5=0
We add all the numbers together, and all the variables
-0.5x+6.5=0
We move all terms containing x to the left, all other terms to the right
-0.5x=-6.5
x=-6.5/-0.5
x=+13

See similar equations:

| 2-500000/x^2=0 | | 4b²+8b+7=4 | | 2y+y=120 | | 38=8u | | M=7/6t+17 | | -50=-3x+5(6x+17) | | 3x+13+x-8+x=180 | | -3Y=2x-9;x-3,0,3 | | 1/3+x/3=5/3 | | 4x-6x-3x+10=-36-2x+5x+14x | | 12^(-3x)=9 | | -3-39×=11x-23 | | 6x^2+148=-2 | | k+3=-16 | | 1/4+y=5/16 | | 3x+4-1=2x+6 | | 11-v=158 | | 169=38-u | | 266=35-x | | -3=2x-9;x=-3.0.3 | | 4x-6x-3x+10=36-2x+5x+14x | | 7n-8-6=-7 | | -4m=-19 | | r/17=-2 | | 10.5=3.5•w | | x=35+39 | | x(x=3)=70 | | r-2=r+18 | | 3^3x=147^x | | 2x-4+2x=44 | | 4x-x=33 | | 9x-4=5x+12x+1≤3 |

Equations solver categories